DAMPAK PERTIMBANGAN EKONOMIS TERHADAP TATA RUANG KOTA JAKARTA DAN BOPUNJUR - Samadikun, Budi Prasetyo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
The Â uncontrollable Â urban Â growth Â become Â serious Â implication Â to Â the Â environment Â and urbanÂ economy. Jakarta as a capital city of Indonesia has growing significantly from metropolitan toÂ megapolitan Â city. Â This Â growth Â also Â followed Â by Â environment Â degradation, Â which Â caused Â by changing of Â urban planology that doesnâ€™t match with the policy of the last government. JakartaÂ coastal reclamation Â and Â the Â changing Â of Â Bopunjurâ€™s Â (Bogor, Â Puncak, Â Cianjur) Â function Â as Â aÂ conservation area are the real evidence, that have occured some colaboration and co-operation Â between Â government as Â a Â policy Â maker Â and Â contractor Â as Â a Â constructor. Â The Â priority Â ofÂ economic consideration by all stakeholders make environment become â€œdyingâ€ Â from day to day.